2023
DOI: 10.1088/1361-6463/acc5f4
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectional wind piezoelectric energy harvesting

Abstract: A novel energy harvester based on vortex-induced vibration (VIV) of the sphere and piezoelectric effect is proposed to efficiently gather wind energy from all horizontal directions. An elastically-supported foam sphere is vertically arranged and considerably oscillates in the cross-flow direction when the wind speed is in the lock-in region. A piezoelectric beam is attached to the supported sphere by a spring and deforms periodically around the original buckling state, thereby converting kinetic energy into el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The experiment demonstrated that the prototype had an extended range of incident wind directions. Zhang et al [22] and Meng et al [23] established a novel spherical bluff body to scavenge the wind energy from multiple directions based on VIV. Although the above mentioned VIV-based harvesters could work in different directions, they only performed effectively in a narrow wind speed range (lock-in region), restricting their efficiencies and outputs.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment demonstrated that the prototype had an extended range of incident wind directions. Zhang et al [22] and Meng et al [23] established a novel spherical bluff body to scavenge the wind energy from multiple directions based on VIV. Although the above mentioned VIV-based harvesters could work in different directions, they only performed effectively in a narrow wind speed range (lock-in region), restricting their efficiencies and outputs.…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric energy harvesting technology, a common method of sustainable clean energy from the external environment, provides idea for power supplying of sensors in water hydraulic system. It is widely used in the field of wind energy [6,7], tidal energy [8], water energy [9,10] and mechanical vibration [11] due to its high energy conversion efficiency, wide applicability and stability. On the other hand, pressure pulsation often occurs in the pipeline of water hydraulic system, which can cause vibration and noise, but also exhibits huge vibration energy harvesting potential [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The present work aims at clean and free power generation at macro-scale using piezoelectric harvesters. The various sources for piezoelectric power generation are human motion , Song et al 2019, Zhang et al 2021, Sirigireddy and Eladi 2022a, vehicular movement (Ansari and Karami 2015, Yang et al 2017, Khalili et al 2022, mechanical vibrations (Roundy andWright 2004, Grzybek andMicek 2019), flow-induced vibrations (Wang et al 2021, Zhang et al 2023, bridge oscillations (Zhang et al 2022) etc. The mechanical energy from these sources are converted into electrical energy using a PEH.…”
Section: Introductionmentioning
confidence: 99%